QuikClimb Rock Gym / Azman Azlan... [et al.] - Azlan, Azman; M Zin, Mohd Afiq; Esmadol, Mohd Irfan; Beddu, Mansur; Sabdin, Mohd Shahiezzan (Faculty of Business Management, Universiti Teknologi MARA, 2010)
In recent years, rock or wall climbing has gone from extreme to mainstream. Every year, more and more people are trying this fun, adventurous sport. Our business, QuikClimb Rock Gym plans to take advantage of this rapid growth by being the first and only climbing gym in Sabah. People in nearly all demographics can and do climb; therefore, it is realistic to use this figure as a starting point for the potential climbing customer market. The key to QuikClimb Rock Gym's success will be to make indoor climbing appealing to the largest cross section of population. More and more Malaysians are looking to pay for experiences rather than just products. QuikClimb Rock Gym will focus on providing each customer with an experience that will make them want to come back for more. QuikClimb Rock Gym will bring unique skills to the company with expertise in building design and construction, and over ten years in the climbing gym industry. Climbing gyms have high start-up costs; however, once built, they enjoy extremely low cost of sales. These high margins will allow QuikClimb Rock Gym to generate strong profits during its first 12 months of operation. QuikClimb Rock Gym's mission is to provide patrons of all ages a fun, safe environment in which to exercise, socialize, and gain new climbing skills. By focusing on these fundamental qualities, the friendly and knowledgeable staff will create an environment that is welcoming to wanting to try climbing for the first time as well as the experienced climber.